PROBLEMS IN TRANSLATING OF ENGLISH PROVERBS INTO UZBEK (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The translation of English proverbs into Uzbek presents a significant and multifaceted linguistic challenge for translators, scholars, and language learners alike. Proverbs, as a form of folklore, encapsulate centuries of collective wisdom, moral lessons, and cultural identity within concise and memorable expressions. When translating English proverbs into Uzbek, one must recognize that these succinct statements are often deeply embedded within the source culture’s worldview, values, and lived experiences. This gives rise to a wide array of issues, ranging from lexical and semantic equivalence to cultural and pragmatic adaptation, all of which come to the fore and require careful consideration.